Medication Beliefs and Associated Factors Among Heart Failure Patients in Yemen and Role of Regimen Complexity: a Cross-Sectional Study - Ramez Abdullah; Ulfa Filliana; I Dewa Agung Diva Candraningrat; Firda Ridhayani; Abdullah Mansoor; Sholikhah Rosvita Oktasari (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2026)
Beliefs about medication influence treatment engagement and outcomes in patients with heart failure, yet evidence from low-resource settings such as Yemen remains limited due to under-supported health care systems and low monitoring in health services. To assess medication beliefs among heart failure patients in Yemen and examine factors associated with necessity and concern beliefs, including medication regimen complexity. A hospital-based cross-sectional study was conducted between December 2023 and February 2024 among heart failure patients attending cardiology outpatient clinics in Sana’a, Yemen after ethical approval from the hospital. Data were collected using structured questionnaires, including the Beliefs About Medication Questionnaire (BMQ-Specific) and the Medication Regimen Complexity Index (MRCI). Multivariable linear regression analyses were performed to identify predictors of medication beliefs. A total of 250 patients were included, with a mean age of 51.08±11.47 years, and 65.2% were male. The median total BMQ score was 38.0 (IQR:35–42). Higher necessity beliefs were independently associated with older age (B=0.046, p=0.029), higher educational status (B=−1.240, p=0.030), and a greater number of prescribed medications (B=0.802, p=0.001), whereas greater medication regimen complexity was negatively associated with necessity beliefs (B=−0.276, p=0.003). Regarding concern beliefs, employment status (B=2.605, p<0.001) and longer duration since diagnosis (>3 years) (B=−1.155, p=0.029) were significant predictors, indicating a mild but significant impact. No significant associations were observed between concern beliefs and age, gender, education, income, number of medications, or regimen complexity. Medication beliefs among heart failure patients in Yemen are shaped by both patient and treatment-related factors. The findings have important implications in clinical practice, both clinical pharmacists and cardiologist can consider patients’ perspective to guide intervention design especially simplifying medication regimens and addressing patient-specific concerns.